DON TOMÁS ALBÁN, IMPRESOR EN MADRID A PRINCIPIOS DEL SIGLO XIX - Manuel Morán Orti (Cuadernos de Ilustración y Romanticismo)
In this article a provisional reconstruction of the trajectory of Don Tomás Albán is carried out, printer who worked in Madrid at the beginning of the 19th century. Through his personal conduct and through his impressions, he was politically and ideologically signified by his adherence to the French in the War of Independence and to the liberal regime during the Triennium 1820 to 1823. Albán ended up transcending his establishment during the absolutist restoration.